Spherical cracking catalyst, preparation method thereof and application of spherical cracking catalyst in direct catalytic cracking reaction of waste plastics

Through the development and application of spherical cracking catalysts, the combination of SAPO-34 molecular sieve and alumina is used to solve the problem of insufficient low-carbon olefin content in waste plastics, and efficient chemical raw materials are achieved, which is suitable for industrial applications.

CN119114151APending Publication Date: 2024-12-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310678194.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the low-carbon olefin content is relatively small in chemical recycling and utilization of waste plastics, making it difficult to effectively produce high-quality chemical raw materials.

Method used

A spherical cracking catalyst, including SAPO-34 molecular sieve and alumina, was developed, prepared by oil ammonia column molding method, and was used for direct catalytic cracking reaction of waste plastics to improve the diffusion performance and activity of the catalyst.

Benefits of technology

It realizes efficient conversion of waste plastics into low-carbon olefins, improves the production efficiency and quality of chemical raw materials, solves the problem of insufficient content of low-carbon olefins, and has good economic benefits and mild process conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114151A_ABST
    Figure CN119114151A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalyst preparation and the field of waste high polymer material recycling, and discloses a spherical cracking catalyst, a preparation method thereof and application of the spherical cracking catalyst in direct catalytic cracking reaction of waste plastics. The spherical cracking catalyst comprises a spherical precursor and a metal oxide, the spherical precursor comprises an SAPO-34 molecular sieve and aluminum oxide, and based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 20-50 wt%, and the content of the aluminum oxide is 50-80 wt%. The spherical cracking catalyst is applied to a reaction for preparing low-carbon olefin through direct catalytic cracking of waste plastics, so that the problem of recycling of the waste plastics is solved, and the yield of the important chemical raw material low-carbon olefin is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalyst preparation and the field of recycling of waste polymer materials, and in particular to a spherical cracking catalyst and a preparation method thereof, and application thereof in direct catalytic cracking reaction of waste plastics. Background Art

[0002] Plastic products are characterized by light weight, high strength, corrosion resistance, good chemical stability, easy processing, and beautiful and practical appearance. They are widely used in various fields around the world. However, plastics are difficult to degrade naturally. Although conventional landfill technology requires little investment and is simple to operate, it will occupy a large amount of land and cause land pollution. Although incineration technology can achieve the reduction requirements and recover some energy at the same time, this process is prone to release a large amount of hydrocarbons, nitrides, sulfides and highly toxic substances, which directly threaten human and ecological health. Therefore, the recycling and high-value utilization of waste plastics as a measure to save energy and protect the environment has been widely valued by countries around the world. The methods for recycling and utilizing waste plastics mainly include classified recycling, preparation of monomer raw materials, production of clean fuel and use for power generation.

[0003] In the prior art, the chemical recycling scheme for waste plastics is mainly waste plastic cracking technology. There are three basic methods for waste plastic cracking, namely: thermal cracking (one-stage method), catalytic cracking (one-stage method) and thermal cracking-catalytic modification (two-stage method). The earliest developed waste plastic cracking technology is thermal cracking technology. This technology refers to a thermal conversion process in which a thermochemical decomposition reaction occurs under high temperature and anaerobic conditions to convert large molecular weight organic matter in waste plastic products into small molecular weight liquids, fuel gas, coke and other substances. The reaction temperature of this process is generally controlled at 350-900°C. If a catalyst is added during the thermal cracking process, it is a catalytic thermal cracking technology, which can not only reduce the cracking temperature, but also improve product performance. The thermal cracking-catalytic modification method is an improvement on the catalytic cracking method. After the waste plastic is thermally cracked, a catalyst is used to catalytically modify the cracking gas. This method has higher product quality, more flexible operation and lower operating costs than the thermal cracking method and the catalytic cracking method, but the process is more complicated.

[0004] Cracking technology has wide flexibility in treating waste plastics and good energy recovery, and is one of the waste plastics treatment technologies with broad application prospects. In the existing technology, the products produced by the one-step thermal cracking method and the one-step catalytic cracking method are mainly fuel oil, and only a small amount of low-carbon olefins (ethylene, propylene, butene) can be obtained. If a large amount of low-carbon olefins is required, a two-stage method of thermal cracking-catalytic reforming is required.

[0005] Therefore, exploring a new chemical recycling process to produce pure and high-quality final products is an important research direction for plastic waste treatment. Summary of the invention

[0006] The purpose of the present invention is to provide a spherical cracking catalyst and a preparation method thereof as well as an application in a direct catalytic cracking reaction of waste plastics in view of the defect problem that the content of light olefins recovered in the current chemical recycling of waste plastics is low. The spherical cracking catalyst is applied to the direct catalytic cracking reaction of waste plastics to produce light olefins, which not only solves the problem of recycling waste plastics, but also increases the production of light olefins, which are important chemical raw materials.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a spherical cracking catalyst, wherein the spherical cracking catalyst comprises a spherical precursor and a metal oxide, the spherical precursor comprises a SAPO-34 molecular sieve and alumina, and based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 20-50% by weight, and the content of the alumina is 50-80% by weight.

[0008] The second aspect of the present invention provides a method for preparing a spherical cracking catalyst, wherein the preparation method comprises: mixing a spherical precursor with an aqueous solution of a metal oxide precursor and conducting a contact reaction; and then removing water, drying and calcining to obtain a spherical cracking catalyst, wherein the spherical precursor comprises SAPO-34 molecular sieve and alumina, and based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 20-50% by weight, and the content of the alumina is 50-80% by weight.

[0009] The third aspect of the present invention provides a spherical cracking catalyst prepared by the above-mentioned preparation method.

[0010] A fourth aspect of the present invention provides an application of the aforementioned spherical cracking catalyst in the direct catalytic cracking of waste plastics to produce light olefins.

[0011] Through the above technical solution, the technical solution of the present invention has the following advantages:

[0012] (1) The spherical cracking catalyst provided by the present invention has a regular shape and high strength, and is suitable for industrial production.

[0013] (2) The SAPO-34 microporous molecular sieve, alumina precursor and metal salt in the raw materials for preparing the spherical cracking catalyst provided by the present invention are all low-priced materials. The prepared spherical cracking catalyst has low cost and is suitable for large-scale industrial production.

[0014] (3) The spherical cracking catalyst provided by the present invention includes SAPO-34 microporous molecular sieve (content not higher than 50%) and alumina (content not lower than 50%) with appropriate acidic centers on the surface, and has a stable structure and good high temperature resistance. During the cracking reaction, the catalyst surface can provide appropriate acidic active centers and ensure the rapid diffusion of raw materials and product molecules in the pores of alumina.

[0015] (4) The spherical cracking catalyst provided by the present invention can convert waste plastics into light olefins in one step when used for direct catalytic cracking of waste plastics to produce light olefins, which is a new method for chemical recycling of waste plastics. It not only solves the problem of recycling waste plastics, but also increases the production of light olefins, an important chemical raw material, and has good economic benefits.

[0016] (5) When the spherical cracking catalyst provided by the present invention is used for the direct catalytic cracking of waste plastics to produce light olefins, the process conditions are mild, the operation is easy, and the requirements for the reaction device are not high.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0019] Figure 1 is a wide-angle X-ray diffraction (XRD) spectrum of the spherical cracking catalyst A of Example 1;

[0020] Figure 2 This is the pore size distribution diagram of the spherical cracking catalyst A of Example 1. DETAILED DESCRIPTION

[0021] As described above, the first aspect of the present invention provides a spherical cracking catalyst, wherein the spherical cracking catalyst comprises a spherical precursor and a metal oxide, the spherical precursor comprises SAPO-34 molecular sieve and alumina, and based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 20-50% by weight, and the content of the alumina is 50-80% by weight.

[0022] The inventors of the present invention have found that in the prior art, there is no process for directly catalytic cracking of waste plastics to produce low-carbon olefins (including ethylene, propylene, and butene), nor is there a catalyst system specifically developed for catalytic cracking reactions of waste plastics. The spherical cracking catalyst developed by the inventors of the present invention can fill the gap in the above-mentioned technology.

[0023] On the one hand, the inventors of the present invention have found that the catalyst used for the direct preparation of light olefins by catalytic cracking of waste plastics needs to have a certain acidity, and in addition, the catalyst for catalytic cracking of waste plastics also needs to have good thermal stability. SAPO-34 molecular sieve not only has suitable acidity, but also has good thermal stability (still able to maintain crystal phase stability under 600°C high temperature conditions), and is a more suitable catalyst for catalytic cracking of waste plastics. However, the pore size of SAPO-34 molecular sieve is generally around 0.4nm, and the pore volume is also relatively small (about 0.3ml / g), which seriously limits the diffusion of raw material molecules, intermediate species and final products during the reaction process. Since the molecular weight of waste plastic products is large and the molecular chain is relatively long, materials with large pore diameter channels are more conducive to the smooth progress of the reaction. If only SAPO-34 molecular sieve is used as a cracking catalyst, in the cracking reaction process of waste plastic products, it is difficult for the reactant molecules and product molecules with larger sizes to diffuse between narrow channels, which not only affects the contact between the reactant and the active center, but also easily leads to the occurrence of side reactions such as deep dehydrogenation, thereby leading to the decline of catalyst performance and the generation of carbon deposition. Compared with microporous molecular sieves such as SAPO-34 molecular sieve, the pore size of γ-alumina is larger (the average pore size can reach more than 5nm) and the pore volume is larger (generally not less than 0.5ml / g), which is very suitable for catalytic reactions involving macromolecules. In addition, the price of alumina is low, which can reduce the cost of catalyst products as a whole. However, the surface of alumina contains only a small amount of silanol groups, and the acidity is extremely weak. If alumina is used as a cracking catalyst to catalyze the conversion reaction of waste plastics, the catalytic performance is poor. The inventors of the present invention found in the development and research of waste plastic cracking catalysts that if the structural advantages of γ-alumina materials and the surface acidic centers of SAPO-34 molecular sieves are comprehensively utilized, the internal diffusion performance in the reaction can be significantly improved and the catalytic efficiency can be improved.

[0024] On the other hand, the inventors of the present invention have found that if a certain proportion of alumina and SAPO-34 molecular sieves are simply mechanically mixed to prepare a waste plastic cracking catalyst, the effect of improving the catalyst performance is not very obvious, because the alumina and SAPO-34 molecular sieves are not mixed evenly, and it is difficult to effectively promote diffusion during the reaction. Therefore, the inventors of the present invention have found through research that the spherical precursor micropore channels (mainly provided by SAPO-34 molecular sieves) and mesopore channels (mainly provided by γ-alumina) prepared by uniformly mixing SAPO-34 molecular sieve powder with alumina precursors, ball milling, beating, and co-oil column molding are uniformly distributed, which is beneficial to the diffusion during the catalytic cracking reaction of waste plastics, thereby effectively improving the catalyst performance.

[0025] According to the present invention, based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 25-45% by weight, and the content of the alumina is 55-75% by weight; preferably, based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 30-40% by weight, and the content of the alumina is 60-70% by weight.

[0026] According to the present invention, the specific surface area of ​​the spherical precursor is 320-450m 2 / g, and a pore volume of 0.45-0.65 mL / g; preferably, the specific surface area of ​​the spherical precursor is 350-420 m 2 / g, and a pore volume of 0.5-0.6 mL / g; more preferably, the specific surface area of ​​the spherical precursor is 366-405 m 2 / g, and the pore volume is 0.53-0.57mL / g.

[0027] According to the present invention, the average particle diameter of the spherical precursor is 1.5-3.5 mm, and the average particle strength is 20-80 N / particle; preferably, the average particle diameter of the spherical precursor is 2.2-2.8 mm, and the average particle strength is 28-55 N / particle; more preferably, the average particle diameter of the spherical precursor is 2.3-2.7 mm, and the average particle strength is 40-53 N / particle.

[0028] According to the present invention, based on the total weight of the spherical cracking catalyst, the content of the spherical precursor is 93-99% by weight, and the content of the metal oxide is 1-7% by weight; preferably, based on the total weight of the spherical cracking catalyst, the content of the spherical precursor is 94-98% by weight, and the content of the metal oxide is 2-6% by weight; more preferably, based on the total weight of the spherical cracking catalyst, the content of the spherical precursor is 95-97% by weight, and the content of the metal oxide is 3-5% by weight. In the present invention, the use of the above-mentioned specific contents of each component can make the prepared spherical cracking catalyst have better catalytic activity and higher selectivity for light olefins when used for the direct catalytic cracking of waste plastics to prepare light olefins.

[0029] According to the present invention, the metal oxide is selected from one or more of alkaline earth metal oxides, transition metal oxides and rare earth metal oxides;

[0030] Preferably, the metal oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide, barium oxide, zinc oxide, copper oxide, cobalt oxide, cerium oxide, lanthanum oxide and zirconium dioxide.

[0031] According to the present invention, the method for preparing the spherical precursor comprises:

[0032] (1) mixing an alumina precursor and a SAPO-34 molecular sieve and then ball milling the mixture to obtain a mixed powder;

[0033] (2) contacting the mixed powder with an acidic aqueous solution to obtain a mixed sol;

[0034] (3) dropping the mixed sol into an oil-ammonia column forming device, and subjecting the mixed sol to spherical gel after sphering and aging treatment;

[0035] (4) The spherical gel is washed, dried and calcined to obtain a spherical precursor.

[0036] According to the present invention, the alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide gel, aluminum sol, gibbsite and boehmite, preferably pseudo-boehmite. In the present invention, specifically, the pseudo-boehmite is more preferably: pseudo-boehmite powder of model P-DF-09-LSi (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​286m 2 / g, pore volume 1.08cm 3 / g), Pseudo-boehmite powder of model P-DF-07-LSi (produced by Shandong Aluminum Co., Ltd., with a specific surface area of ​​249m 2 / g, pore volume 0.82cm 3 / g), macroporous pseudo-boehmite powder of model PB-0101 (produced by Zibo Hengqi Powder New Material Co., Ltd., with a specific surface area of ​​327m 2 / g, pore volume 1.02cm 3 / g).

[0037] In the present invention, the aluminum oxide precursor can be commercially available.

[0038] According to the present invention, the ball milling is carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball mill jar, and for a ball mill jar of 100-300 mL, 2-8 grinding balls can usually be used; the material of the grinding balls is agate or polytetrafluoroethylene, preferably agate. The conditions of the ball milling include: the rotation speed of the grinding balls can be 200-600r / min, preferably 300-500r / min; the temperature in the ball mill jar can be 30-90°C, preferably 40-80°C; the ball milling time can be 5-50h, preferably 8-24h.

[0039] According to the present invention, the acidic aqueous solution can be an organic acid aqueous solution or an inorganic acid aqueous solution, preferably one or more of a formic acid aqueous solution, an acetic acid aqueous solution, a citric acid aqueous solution, a nitric acid aqueous solution, and a hydrochloric acid aqueous solution, more preferably a nitric acid aqueous solution or a citric acid aqueous solution; the mass concentration of the acidic aqueous solution can be 0.2-10%, preferably 0.5-5%.

[0040] According to the present invention, the weight ratio of the aluminum oxide precursor, the SAPO-34 molecular sieve and the acidic aqueous solution is 1: (0.1-1.0): (2.1-3.0), preferably 1: (0.2-0.6): (2.3-2.5).

[0041] According to the present invention, in the oil-ammonia column forming device, the oil-ammonia column is placed in the oil-ammonia column forming device, and the oil-ammonia column forming device is a carrier / catalyst forming device that utilizes the surface tension of the liquid to shrink the sol into a ball in the oil layer and dehydrate and shape it in the alkaline water layer. In the present invention, the surface tension only needs to be able to ensure the formation of the sol; in addition, dehydration relies on the reaction of ammonia in the oil column with the acid in the sol to remove excess water in the raw material ball under certain temperature conditions. Surface tension and dehydration are the principles of the oil-ammonia column forming method, and ball formation and dehydration are achieved by relying on the conditions of sol preparation, acid addition amount, ratio, stirring, speed, temperature, oil phase and water phase ratio, etc. during the forming process.

[0042] In the present invention, the inventors of the present invention used the oil-ammonia column molding method for the first time in the waste plastic cracking catalyst molding process, and unexpectedly found that the prepared spherical precursor microporous channels (mainly provided by SAPO-34 molecular sieve) and mesoporous channels (mainly provided by γ-alumina) are uniformly distributed, which is beneficial to the diffusion during the catalytic cracking reaction of waste plastics, thereby effectively improving the catalyst performance.

[0043] In the present invention, the oil-ammonia column forming device is an XF1616 oil-ammonia column forming test device produced by Sichuan Zhiyan Technology Co., Ltd.

[0044] According to the present invention, the oil phase of the oil-ammonia column forming device is selected from one or more of transformer oil, silicone oil, vacuum pump oil, liquid paraffin, white oil, gasoline, engine oil and petroleum ether, preferably one or more of transformer oil, vacuum pump oil and silicone oil.

[0045] According to the present invention, the water phase of the oil-ammonia column forming device is an ammonia solution containing a nonionic surfactant and a low-carbon alcohol. The nonionic surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, preferably peregal O-25 (fatty alcohol polyoxyethylene ether, molecular formula C 62-68 H 126-138O 26 ), P123 (a triblock copolymer, the full name is: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, the specific molecular formula is: EO 20 PO 70 EO 20 , molecular weight of 5800), F108 (a triblock copolymer, full name: polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, specific molecular formula: EO 133 PO 50 EO 133 , molecular weight is 14600) one or more; the low-carbon alcohol is one or more of C1-C4 monohydric alcohol, dihydric alcohol and trihydric alcohol, preferably one or more of ethanol, ethylene glycol and isopropanol.

[0046] According to the present invention, in step (3), the conditions for ball formation may include: the sol ball dropping speed is 10-300 drops / minute, and the oil-ammonia column temperature is 20-120°C.

[0047] According to the present invention, in step (3), the aging conditions may include: a temperature of 20-120° C. and a time of 1-10 h.

[0048] According to the present invention, in step (4), the washing method is not particularly limited, and the spherical product can be washed with deionized water for multiple times until the pH value of the washing liquid is 7. Generally, the number of washing times with deionized water is 5-10 times.

[0049] According to the present invention, in step (4), the drying conditions may include: a temperature of 70-150° C. and a time of 3-20 h.

[0050] According to the present invention, in step (4), the calcination conditions may include: a temperature of 500-700° C. and a time of 2-16 hours.

[0051] According to the present invention, the specific surface area of ​​the spherical cracking catalyst is 300-430m 2 / g, pore volume is 0.40-0.64mL / g, pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 0.3-0.5nm and 7-12nm, respectively. In the present invention, when the spherical cracking catalyst has the aforementioned specific structural parameters, it can be used for the direct catalytic cracking of waste plastics to prepare light olefins with better catalytic activity and higher light olefin selectivity.

[0052] The second aspect of the present invention provides a method for preparing a spherical cracking catalyst, wherein the preparation method comprises: mixing a spherical precursor with an aqueous solution of a metal oxide precursor and conducting a contact reaction; and then removing water, drying and calcining to obtain a spherical cracking catalyst, wherein the spherical precursor comprises SAPO-34 molecular sieve and alumina, and based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 20-50% by weight, and the content of the alumina is 50-80% by weight.

[0053] According to the present invention, the metal oxide precursor is selected from inorganic salts containing alkaline earth metals, transition metals and rare earth metals; preferably, the metal oxide precursor is selected from nitrates containing magnesium, calcium, strontium, barium, zinc, copper, cobalt, cerium, lanthanum and zirconium.

[0054] According to the present invention, the mass concentration of the metal oxide precursor aqueous solution is 0.35-5.0%.

[0055] According to the present invention, the weight ratio of the spherical precursor to the metal oxide precursor aqueous solution is 1:(4-60).

[0056] According to the present invention, the contact reaction conditions include: temperature of 10-100° C. and time of 0.5-50 h.

[0057] According to the present invention, the calcination conditions include: a temperature of 400-700° C. and a time of 2-20 hours.

[0058] The third aspect of the present invention provides a spherical cracking catalyst prepared by the above-mentioned preparation method.

[0059] A fourth aspect of the present invention provides an application of the aforementioned spherical cracking catalyst in the direct catalytic cracking of waste plastics to produce light olefins.

[0060] According to the present invention, the application comprises: contacting the spherical cracking catalyst with the powder of the waste plastic to react.

[0061] According to the present invention, the contact conditions include: temperature of 420-580° C., pressure of 0.01-1 MPa, and contact time of 0.5-12 h.

[0062] According to the present invention, the weight ratio of the spherical cracking catalyst to the waste plastic powder is 1:(0.5-50).

[0063] According to the present invention, the waste plastic is waste polyethylene plastic (polyethylene waste plastic).

[0064] The present invention will be described in detail below through examples.

[0065] In the following examples and comparative examples:

[0066] (1) The wide-angle XRD test of the samples was carried out on an X'Pert MPD X-ray powder diffractometer produced by Philips of the Netherlands, using a Cu Kα target and a scanning range of 2θ=5-90°.

[0067] (2) The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 350°C for 4 hours before measurement. The specific surface area of ​​the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.

[0068] (3) The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0069] (4) The drying oven was manufactured by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0070] (5) The muffle furnace is manufactured by CARBOLITE, model CWF1100.

[0071] (6) The SAPO-34 molecular sieve used in the examples and comparative examples was purchased from Zhuoran Environmental Protection Technology (Dalian) Co., Ltd., and other reagents were purchased from Sinopharm Chemical Reagent Co., Ltd., and the reagent purity was analytical grade.

[0072] Example 1

[0073] This example is intended to illustrate the spherical cracking catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.

[0074] (1) Preparation of spherical precursors

[0075] 46 g of P-DF-09-LSi pseudo-boehmite powder was mixed with 18 g of SAPO-34 molecular sieve (specific surface area 634 m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 60°C, the speed of the grinding balls was 400r / min, and the ball milling time was 16h;

[0076] The powder obtained after ball milling was mixed with 110 g of 1% dilute nitric acid and stirred for 8 h to prepare a sol;

[0077] The sol is dripped into an oil-ammonia column forming device at a sol dripping speed of 120 drops / minute. The oil phase of the oil-ammonia column forming device is transformer oil, the water phase is an ammonia solution containing peregal and ethylene glycol, and the temperature of the oil-ammonia column is 60°C;

[0078] After the sol dropping ball is completed, the sol ball is aged at 60°C for 6 hours, washed with deionized water 8 times, dried at 120°C for 12 hours, and then calcined at 600°C for 10 hours to obtain a spherical precursor A.

[0079] Based on the total weight of the spherical precursor A, the content of alumina is 65 wt % and the content of SAPO-34 molecular sieve is 35 wt %.

[0080] The specific surface area of ​​spherical precursor A is 385m 2 / g, pore volume is 0.55ml / g, average particle diameter is 2.5mm, and average particle strength is 48.7N / particle.

[0081] (2) Preparation of spherical cracking catalyst

[0082] 2.56 g of magnesium nitrate hexahydrate was dissolved in 100 g of distilled water to prepare an aqueous solution. 9.6 g of spherical precursor A was added to the aqueous solution, stirred at 60° C. for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a spherical cracking catalyst A.

[0083] Based on the total weight of the spherical cracking catalyst A, the content of the spherical precursor was 96.0% by weight and the content of magnesium oxide was 4.0% by weight.

[0084] The specific surface area of ​​spherical cracking catalyst A is 370m 2 / g, pore volume 0.53cm 3 / g.

[0085] Figure 1 This is the wide-angle XRD spectrum of spherical cracking catalyst A. Figure 1The spectrum shows that the X-ray diffraction angles of the sample are mainly: 2θ≈9.6°, 13.0°, 15.9°, 20.7°, 30.6°, 31.1°, 36.9°, 39.5°, 45.9° and 66.9°, among which the six diffraction signals located at 2θ≈9.6°, 13.0°, 15.9°, 20.7°, 30.6° and 31.1° are consistent with the diffraction spectrum of SAPO-34 molecular sieve; the four diffraction signals located at 2θ≈36.9°, 39.5°, 45.9° and 66.9° are consistent with the diffraction spectrum of γ-Al2O3, indicating that the basic crystal phase structure of SAPO-34 molecular sieve does not change significantly after the spherical cracking catalyst A is calcined at 600°C during the catalyst preparation process, and the pseudo-boehmite mainly exists in the γ-Al2O3 crystal phase after dehydration.

[0086] In addition, there is no diffraction signal corresponding to magnesium oxide in the wide-angle XRD spectrum, indicating that the metal oxide is uniformly dispersed on the catalyst.

[0087] Figure 2 is the pore size distribution diagram of spherical cracking catalyst A. Figure 2 The spectrum shows that the sample has an obvious dual-pore structure, with dual pore diameters of 0.4nm and 9.7nm respectively. Among them, the pore with the most probable pore diameter of 0.4nm is provided by SAPO-34 molecular sieve, and the mesoporous pore with the most probable pore diameter of 9.7nm is provided by γ-Al2O3. Since SAPO-34 molecular sieve has a regular topological structure, the pore size distribution of 0.4nm is relatively concentrated; while the γ-Al2O3 pore structure obtained by calcining pseudo-boehmite is disordered in both short-range and long-range, so the pore size distribution is relatively wide.

[0088] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0089] The catalytic cracking reaction performance of waste plastics of spherical cracking catalyst A was evaluated in a fixed bed reactor. The loading amount of spherical cracking catalyst A was 5.0 g, the loading amount of polyethylene waste plastic was 55.0 g, the reaction temperature was 520°C, the reaction pressure was 0.1 MPa, the reaction time was 2 hours, and after the product was cooled and the gas-liquid was separated, the gas composition was analyzed by an Agilent 6890 gas chromatograph equipped with an Al2O3-S capillary column and a hydrogen flame detector (FID), and the quantitative analysis was performed by program heating and correction factors; the liquid composition was analyzed by an Agilent 6890 gas chromatograph equipped with a PONA column. The reaction results are shown in Table 1.

[0090] Example 2

[0091] This example is intended to illustrate the spherical cracking catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.

[0092] (1) Preparation of spherical precursors

[0093] 50g of P-DF-07-LSi pseudo-boehmite powder was mixed with 15g of SAPO-34 molecular sieve (specific surface area 634m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and three agate grinding balls with a diameter of 2mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 450r / min, and the ball milling time was 12h;

[0094] The powder obtained after ball milling was mixed with 120 g of 2% citric acid and stirred for 12 h to prepare a sol;

[0095] The sol was dripped into the oil-ammonia column forming device at a sol dripping speed of 180 drops / minute. The oil phase of the oil-ammonia column forming device was silicone oil, the water phase was an ammonia solution containing F108 and isopropanol, and the temperature of the oil-ammonia column was 80°C.

[0096] After the sol dropping ball is completed, the sol ball is aged at 80°C for 4h, washed with deionized water 6 times, dried at 100°C for 16h, and then calcined at 600°C for 8h to obtain the spherical precursor B.

[0097] Based on the total weight of the spherical precursor B, the content of alumina was 70 wt % and the content of SAPO-34 molecular sieve was 30 wt %.

[0098] The specific surface area of ​​spherical precursor B is 366m 2 / g, pore volume is 0.57ml / g, average particle diameter is 2.7mm, and average particle strength is 51.3N / particle.

[0099] (2) Preparation of spherical cracking catalyst

[0100] 0.88 g of calcium nitrate was dissolved in 50 g of distilled water to prepare an aqueous solution. 9.7 g of spherical precursor B was added to the aqueous solution, stirred at 80° C. for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130° C. for 3 h, and then calcined at 600° C. for 3 h to obtain a spherical cracking catalyst B.

[0101] Based on the total weight of the spherical cracking catalyst B, the content of the spherical precursor was 97.0% by weight and the content of calcium oxide was 3.0% by weight.

[0102] The specific surface area of ​​spherical cracking catalyst B is 355m 2 / g, pore volume 0.55cm 3 / g.

[0103] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0104] The reaction performance of the spherical cracking catalyst B was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0105] Example 3

[0106] This example is intended to illustrate the spherical cracking catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.

[0107] (1) Preparation of spherical precursors

[0108] 43g of PB-0101 pseudo-boehmite powder was mixed with 20g of SAPO-34 molecular sieve (specific surface area 634m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 3mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 30°C, the speed of the grinding balls was 500r / min, and the ball milling time was 4h;

[0109] The powder obtained after ball milling was mixed with 100 g of 0.5% dilute nitric acid and stirred for 16 h to prepare a sol;

[0110] The sol was dripped into the oil-ammonia column forming device at a sol dripping speed of 10 drops / minute. The oil phase of the oil-ammonia column forming device was vacuum pump oil, the water phase was an ammonia solution containing P123 and ethanol, and the temperature of the oil-ammonia column was 20°C.

[0111] After the sol dropping ball was completed, the sol ball was aged at 20°C for 10 h, washed with deionized water 5 times, dried at 70°C for 20 h, and then calcined at 650°C for 4 h to obtain the spherical precursor C.

[0112] Based on the total weight of the spherical precursor C, the content of alumina is 60 wt % and the content of SAPO-34 molecular sieve is 40 wt %.

[0113] The specific surface area of ​​spherical precursor C is 405m 2 / g, pore volume is 0.53ml / g, average particle diameter is 2.3mm, and average particle strength is 41.6N / particle.

[0114] (2) Preparation of spherical cracking catalyst

[0115] 0.85 g of barium nitrate was dissolved in 200 g of distilled water to prepare an aqueous solution. 9.5 g of spherical precursor C was added to the aqueous solution, stirred at 30° C. for 20 h, and then the water was removed using a rotary evaporator. The solid product was dried at 80° C. for 20 h, and then calcined at 500° C. for 10 h to obtain a spherical cracking catalyst C.

[0116] Based on the total weight of the spherical cracking catalyst C, the content of the spherical precursor was 95.0% by weight and the content of barium oxide was 5.0% by weight.

[0117] The specific surface area of ​​spherical cracking catalyst C is 385m 2 / g, pore volume 0.50cm 3 / g.

[0118] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0119] The reaction performance of the spherical cracking catalyst C was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0120] Example 4

[0121] This example is intended to illustrate the spherical cracking catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.

[0122] (1) Preparation of spherical precursors

[0123] 53g of P-DF-09-LSi pseudo-boehmite powder was mixed with 13g of SAPO-34 molecular sieve (specific surface area 634m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 60°C, the speed of the grinding balls was 400r / min, and the ball milling time was 16h;

[0124] The powder obtained after ball milling was mixed with 115 g of 1% dilute nitric acid and stirred for 8 h to prepare a sol;

[0125] The sol is dripped into an oil-ammonia column forming device at a sol dripping speed of 120 drops / minute. The oil phase of the oil-ammonia column forming device is transformer oil, the water phase is an ammonia solution containing peregal and ethylene glycol, and the temperature of the oil-ammonia column is 60°C;

[0126] After the sol dropping was completed, the sol balls were aged at 60°C for 6 h, washed with deionized water 8 times, dried at 120°C for 12 h, and then calcined at 550°C for 12 h to obtain spherical precursor D.

[0127] Based on the total weight of the spherical precursor D, the content of alumina was 75 wt % and the content of SAPO-34 molecular sieve was 25 wt %.

[0128] The specific surface area of ​​spherical precursor D is 350 m 2 / g, pore volume is 0.6ml / g, average particle diameter is 2.8mm, and average particle strength is 54.1N / particle.

[0129] (2) Preparation of spherical cracking catalyst

[0130] 0.41 g of strontium nitrate was dissolved in 60 g of distilled water to prepare an aqueous solution. 9.8 g of spherical precursor D was added to the aqueous solution, stirred at 60° C. for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a spherical cracking catalyst D.

[0131] Based on the total weight of the spherical cracking catalyst D, the content of the spherical precursor was 98.0% by weight and the content of strontium oxide was 2.0% by weight.

[0132] The specific surface area of ​​spherical cracking catalyst D is 343m 2 / g, pore volume 0.59cm 3 / g.

[0133] The reaction performance of catalyst D was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0134] Example 5

[0135] This example is intended to illustrate the spherical cracking catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.

[0136] (1) Preparation of spherical precursors

[0137] 39g of PB-0101 pseudo-boehmite powder and 23g of SAPO-34 molecular sieve (specific surface area 634m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 3mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 30°C, the speed of the grinding balls was 500r / min, and the ball milling time was 4h;

[0138] The powder obtained after ball milling was mixed with 95 g of 0.5% dilute nitric acid and stirred for 16 h to prepare a sol;

[0139] The sol was dripped into the oil-ammonia column forming device at a sol dripping speed of 10 drops / minute. The oil phase of the oil-ammonia column forming device was vacuum pump oil, the water phase was an ammonia solution containing P123 and ethanol, and the temperature of the oil-ammonia column was 20°C.

[0140] After the sol dropping ball was completed, the sol ball was aged at 20°C for 10 h, washed with deionized water 5 times, dried at 70°C for 20 h, and then calcined at 650°C for 4 h to obtain the spherical precursor E.

[0141] Based on the total weight of the spherical precursor E, the content of alumina was 55 wt % and the content of SAPO-34 molecular sieve was 45 wt %.

[0142] The specific surface area of ​​spherical precursor E is 420 m 2 / g, pore volume is 0.50ml / g, average particle diameter is 2.2mm, and average particle strength is 38.2N / particle.

[0143] (2) Preparation of spherical cracking catalyst

[0144] 2.2 g of zinc nitrate hexahydrate was dissolved in 300 g of distilled water to prepare an aqueous solution. 9.4 g of spherical precursor E was added to the aqueous solution, stirred at 30° C. for 20 h, and then the water was removed using a rotary evaporator. The solid product was dried at 80° C. for 20 h, and then calcined at 500° C. for 10 h to obtain a spherical cracking catalyst E.

[0145] Based on the total weight of the spherical cracking catalyst E, the content of the spherical precursor was 94.0% by weight and the content of zinc oxide was 6.0% by weight.

[0146] The specific surface area of ​​spherical cracking catalyst E is 395m 2 / g, pore volume 0.47cm 3 / g.

[0147] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0148] The reaction performance of the spherical cracking catalyst E was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0149] Example 6

[0150] This example is intended to illustrate the spherical cracking catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.

[0151] (1) Preparation of spherical precursors

[0152] 57g of P-DF-09-LSi pseudo-boehmite powder was mixed with 10g of SAPO-34 molecular sieve (specific surface area 634m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 60°C, the speed of the grinding balls was 400r / min, and the ball milling time was 16h;

[0153] The powder obtained after ball milling was mixed with 120 g of 1% dilute nitric acid and stirred for 8 h to prepare a sol;

[0154] The sol is dripped into an oil-ammonia column forming device at a sol dripping speed of 120 drops / minute. The oil phase of the oil-ammonia column forming device is transformer oil, the water phase is an ammonia solution containing peregal and ethylene glycol, and the temperature of the oil-ammonia column is 60°C;

[0155] After the sol dropping was completed, the sol balls were aged at 60°C for 6 h, washed with deionized water 8 times, dried at 120°C for 12 h, and then calcined at 550°C for 12 h to obtain spherical precursor F.

[0156] Based on the total weight of the spherical precursor F, the content of alumina is 80 wt % and the content of SAPO-34 molecular sieve is 20 wt %.

[0157] The specific surface area of ​​the spherical precursor F is 320 m 2 / g, pore volume is 0.65ml / g, average particle diameter is 3.2mm, and average particle strength is 64.7N / particle.

[0158] (2) Preparation of spherical cracking catalyst

[0159] 0.27 g of lanthanum nitrate hexahydrate was dissolved in 40 g of distilled water to prepare an aqueous solution. 9.9 g of spherical precursor F was added to the aqueous solution, stirred at 60° C. for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a spherical cracking catalyst F.

[0160] Based on the total weight of the spherical cracking catalyst F, the content of the spherical precursor was 99.0% by weight and the content of lanthanum oxide was 1.0% by weight.

[0161] The specific surface area of ​​spherical cracking catalyst F is 317m 2 / g, pore volume 0.64cm 3 / g.

[0162] The reaction performance of Catalyst F was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0163] Example 7

[0164] This example is intended to illustrate the spherical cracking catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.

[0165] (1) Preparation of spherical precursors

[0166] 36g of PB-0101 pseudo-boehmite powder and 25g of SAPO-34 molecular sieve (specific surface area 634m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 3mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 30°C, the speed of the grinding balls was 500r / min, and the ball milling time was 4h;

[0167] The powder obtained after ball milling was mixed with 92 g of 0.5% dilute nitric acid and stirred for 16 h to prepare a sol;

[0168] The sol was dripped into the oil-ammonia column forming device at a sol dripping speed of 10 drops / minute. The oil phase of the oil-ammonia column forming device was vacuum pump oil, the water phase was an ammonia solution containing P123 and ethanol, and the temperature of the oil-ammonia column was 20°C.

[0169] After the sol dropping ball is completed, the sol ball is aged at 20°C for 10 h, washed with deionized water 5 times, dried at 70°C for 20 h, and then calcined at 650°C for 4 h to obtain the spherical precursor G.

[0170] Based on the total weight of the spherical precursor G, the content of alumina is 50 weight % and the content of SAPO-34 molecular sieve is 50 weight %.

[0171] The specific surface area of ​​the spherical precursor G is 450 m 2 / g, pore volume is 0.45ml / g, average particle diameter is 1.8mm, and average particle strength is 26.3N / particle.

[0172] (2) Preparation of spherical cracking catalyst

[0173] 1.75 g of cerium nitrate was dissolved in 500 g of distilled water to prepare an aqueous solution. 9.3 g of spherical precursor G was added to the aqueous solution, stirred at 30° C. for 20 h, and then the water was removed using a rotary evaporator. The solid product was dried at 80° C. for 20 h, and then calcined at 500° C. for 10 h to obtain a spherical cracking catalyst G.

[0174] Based on the total weight of the spherical cracking catalyst G, the content of the spherical precursor was 93.0% by weight and the content of cerium oxide was 7.0% by weight.

[0175] The specific surface area of ​​spherical cracking catalyst G is 417m 2 / g, pore volume 0.42cm 3 / g.

[0176] The reaction performance of the spherical cracking catalyst G was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0177] Comparative Example 1

[0178] (1) Preparation of spherical precursors

[0179] 64 g of P-DF-09-LSi pseudo-boehmite powder was mixed with 5 g of SAPO-34 molecular sieve (specific surface area 634 m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 60°C, the speed of the grinding balls was 400r / min, and the ball milling time was 16h;

[0180] The powder obtained after ball milling was mixed with 128 g of 1% dilute nitric acid and stirred for 8 h to prepare a sol;

[0181] The sol is dripped into an oil-ammonia column forming device at a sol dripping speed of 120 drops / minute. The oil phase of the oil-ammonia column forming device is transformer oil, the water phase is an ammonia solution containing peregal and ethylene glycol, and the temperature of the oil-ammonia column is 60°C;

[0182] After the sol dropping was completed, the sol balls were aged at 60°C for 6 h, washed with deionized water 8 times, dried at 120°C for 12 h, and then calcined at 550°C for 12 h to obtain the spherical precursor D1.

[0183] Based on the total weight of the spherical precursor D1, the content of alumina was 90 wt % and the content of SAPO-34 molecular sieve was 10 wt %.

[0184] The specific surface area of ​​the spherical precursor D1 is 290 m 2 / g, pore volume is 0.67ml / g, average particle diameter is 3.9mm, and average particle strength is 84.0N / particle.

[0185] (2) Preparation of spherical cracking catalyst

[0186] 0.13 g of cerium nitrate hexahydrate was dissolved in 40 g of distilled water to prepare an aqueous solution. 10.0 g of spherical precursor D1 was added to the aqueous solution, stirred at 60° C. for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a spherical cracking catalyst D1.

[0187] Based on the total weight of the spherical cracking catalyst D1, the content of the spherical precursor was 99.5% by weight and the content of cerium oxide was 0.5% by weight.

[0188] The specific surface area of ​​spherical cracking catalyst D1 is 289m 2 / g, pore volume 0.66cm 3 / g.

[0189] The reaction performance of the spherical cracking catalyst D1 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0190] Comparative Example 2

[0191] (1) Preparation of spherical precursors

[0192] 18g of PB-0101 pseudo-boehmite powder and 37g of SAPO-34 molecular sieve (specific surface area 634m 2 / g, pore volume of 0.30ml / g) were mixed and transferred to a 200mL ball mill, and 4 agate grinding balls with a diameter of 3mm were placed to start ball milling; wherein, the temperature in the ball mill was controlled at 30°C, the speed of the grinding balls was 500r / min, and the ball milling time was 4h;

[0193] The powder obtained after ball milling was mixed with 86 g of 0.5% dilute nitric acid and stirred for 16 h to prepare a sol;

[0194] The sol was dripped into the oil-ammonia column forming device at a sol dripping speed of 10 drops / minute. The oil phase of the oil-ammonia column forming device was vacuum pump oil, the water phase was an ammonia solution containing P123 and ethanol, and the temperature of the oil-ammonia column was 20°C.

[0195] After the sol dropping ball was completed, the sol ball was aged at 20°C for 10 h, washed with deionized water 5 times, dried at 70°C for 20 h, and then calcined at 650°C for 4 h to obtain the spherical precursor D2.

[0196] Based on the total weight of the spherical precursor D2, the content of alumina was 26 wt % and the content of SAPO-34 molecular sieve was 74 wt %.

[0197] The specific surface area of ​​the spherical precursor D2 is 530 m 2 / g, the pore volume is 0.40ml / g, the particle shape is not regular, the average particle diameter is about 1.3mm, and the average particle strength is 6.4N / particle.

[0198] (2) Preparation of spherical cracking catalyst

[0199] 1.88 g of barium nitrate was dissolved in 600 g of distilled water to prepare an aqueous solution. 8.9 g of spherical precursor D2 was added to the aqueous solution, stirred at 30° C. for 20 h, and then the water was removed using a rotary evaporator. The solid product was dried at 80° C. for 20 h, and then calcined at 500° C. for 10 h to obtain a spherical cracking catalyst D2.

[0200] Based on the total weight of the spherical cracking catalyst D2, the content of the spherical precursor was 89.0% by weight and the content of barium oxide was 11.0% by weight.

[0201] The specific surface area of ​​spherical cracking catalyst D2 is 472m 2 / g, pore volume 0.35cm 3 / g.

[0202] The reaction performance of the spherical cracking catalyst D2 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0203] Comparative Example 3

[0204] (1) Preparation of spherical precursors

[0205] 71 g of P-DF-09-LSi pseudo-boehmite powder was added to a 200 mL ball mill, and four agate grinding balls with a diameter of 2 mm were placed in the mill to start ball milling. The temperature in the mill was controlled at 60°C, the speed of the grinding balls was 400 r / min, and the ball milling time was 16 h.

[0206] The powder obtained after ball milling was mixed with 125 g of 1% dilute nitric acid and stirred for 8 h to prepare a sol;

[0207] The sol is dripped into an oil-ammonia column forming device at a sol dripping speed of 120 drops / minute. The oil phase of the oil-ammonia column forming device is transformer oil, the water phase is an ammonia solution containing peregal and ethylene glycol, and the temperature of the oil-ammonia column is 60°C;

[0208] After the sol dropping ball was completed, the sol ball was aged at 60°C for 6 h, washed with deionized water 8 times, dried at 120°C for 12 h, and then calcined at 600°C for 10 h to obtain the spherical precursor D3.

[0209] The content of aluminum oxide was 100 wt % based on the total weight of the spherical precursor D3.

[0210] The specific surface area of ​​the spherical precursor D3 is 254 m 2 / g, pore volume is 0.69ml / g, average particle diameter is 3.0mm, and average particle strength is 82.7N / particle.

[0211] (2) Preparation of spherical cracking catalyst

[0212] 1.47 g of zinc nitrate hexahydrate was dissolved in 100 g of distilled water to prepare an aqueous solution. 9.6 g of spherical precursor D3 was added to the aqueous solution, stirred at 60° C. for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a spherical cracking catalyst D3.

[0213] Based on the total weight of the spherical cracking catalyst D3, the content of the spherical precursor was 96.0% by weight and the content of magnesium oxide was 4.0% by weight.

[0214] The specific surface area of ​​spherical cracking catalyst D3 is 244m 2 / g, pore volume 0.66cm 3 / g.

[0215] The reaction performance of the spherical cracking catalyst D3 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0216] Comparative Example 4

[0217] The spherical precursor A was prepared according to the method of step (1) in Example 1.

[0218] Eliminate step (2) in Example 1.

[0219] The reaction performance of the spherical precursor A was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0220] Comparative Example 5

[0221] The spherical precursor A was prepared according to the method of step (1) in Example 1.

[0222] (2) Preparation of spherical cracking catalyst

[0223] 1.56 g of nickel nitrate hexahydrate was dissolved in 100 g of distilled water to prepare an aqueous solution. 9.6 g of spherical precursor A was added to the aqueous solution, stirred at 60° C. for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110° C. for 8 h, and then calcined at 550° C. for 6 h to obtain a spherical cracking catalyst D5.

[0224] Based on the total weight of the spherical cracking catalyst D5, the content of the spherical precursor was 96.0% by weight and the content of the nickel oxide was 4.0% by weight.

[0225] The reaction performance of the composite material D5 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0226] Comparative Example 6

[0227] (1) Preparation of spherical precursors

[0228] Instead of using the oil-ammonia column forming device in step (1) of Example 1 to prepare the spherical precursor D6, 46 g of pseudo-boehmite powder of model P-DF-09-LSi was calcined at 600°C for 10 h to obtain 32 g of alumina. The alumina was mixed with 18 g of SAPO-34 molecular sieve (specific surface area of ​​634 m 2 / g, pore volume of 0.30ml / g) were mechanically mixed to prepare catalyst precursor D6. In addition, the catalyst precursor D6 obtained after mechanical mixing was in powder form, not spherical, and had no particle diameter and particle strength.

[0229] Based on the total weight of the catalyst precursor D6, the content of alumina was 64 wt % and the content of SAPO-34 molecular sieve was 36 wt %.

[0230] The specific surface area of ​​the spherical precursor D6 is 351 m 2 / g, and the pore volume is 0.51ml / g.

[0231] (2) Spherical cracking catalyst D6 was prepared according to the preparation method of the spherical cracking catalyst in step (2) of Example 1.

[0232] Based on the total weight of the spherical cracking catalyst D6, the content of the spherical precursor was 96.0% by weight and the content of magnesium oxide was 4.0% by weight.

[0233] (3) The reaction performance of the spherical cracking catalyst D6 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0234] Comparative Example 7

[0235] (1) Preparation of spherical precursors

[0236] The spherical precursor D7 was prepared according to the preparation method of the spherical precursor in step (1) of Example 1, except that the "SAPO-34 molecular sieve" was replaced by the "all-silicon Silicalite-1 molecular sieve" to obtain the spherical precursor D7.

[0237] Based on the total weight of the spherical precursor D7, the content of alumina was 65 wt % and the content of SAPO-34 molecular sieve was 35 wt %.

[0238] The specific surface area of ​​spherical precursor D7 is 287 m 2 / g, pore volume is 0.52ml / g, average particle diameter is 2.5mm, and average particle strength is 43.6N / particle.

[0239] (2) Spherical cracking catalyst D7 was prepared according to the preparation method of the spherical cracking catalyst in step (2) of Example 1.

[0240] Based on the total weight of the spherical cracking catalyst D7, the content of the spherical precursor was 96.0% by weight and the content of magnesium oxide was 4.0% by weight.

[0241] The specific surface area of ​​spherical cracking catalyst D7 is 261m 2 / g, pore volume 0.49cm 3 / g.

[0242] (3) The reaction performance of the spherical cracking catalyst D7 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0243] Table 1

[0244]

[0245]

[0246] It can be seen from the above results that the spherical cracking catalyst provided by the present invention can directly catalyze the conversion of waste plastics into light olefins. The conversion rate of waste plastics is 100%, and the yield of light olefins exceeds 40%.

[0247] In Comparative Example 1, the content of alumina in the spherical precursor is too high, the content of SAPO-34 molecular sieve is too low, and the content of metal oxide used for modification in the cracking catalyst is too low. Due to the small number of active centers for cracking waste plastics on the catalyst and insufficient activation sites during the reaction, the raw material conversion rate and the yield of light olefins are low.

[0248] In Comparative Example 2, the content of alumina in the spherical precursor is too low, and the content of SAPO-34 molecular sieve is too high, resulting in the spherical precursor having low particle shape regularity and low mechanical strength, which does not meet the requirements of industrial production. Moreover, the content of metal oxide used for modification in the cracking catalyst is too high. Due to the fact that the mesoporous channels provided by alumina in the catalyst are relatively few and the active centers are unevenly distributed, the diffusion of reactants and product molecules is hindered during the reaction, resulting in more by-products in the reaction and a lower yield of light olefins.

[0249] In Comparative Example 3, the spherical precursor contains only alumina but no SAPO-34 molecular sieve. Since the number of active acidic centers on the catalyst is small and the acidity is weak, the raw material conversion rate is low and the selectivity of light olefins is not high.

[0250] In Comparative Example 4, only the spherical precursor A was used as a cracking catalyst without adding a metal oxide for modification, resulting in a lower yield of light olefins.

[0251] In Comparative Example 5, nickel oxide is used instead of metal oxide. Since the modification effect of nickel oxide is significantly lower than that of the specific metal oxide of the present invention, the yield of light olefins in the prepared cracking catalyst is lower.

[0252] In Comparative Example 6, the waste plastic cracking catalyst was prepared by simple mechanical mixing of alumina and SAPO-34 molecular sieve, but the catalyst performance improvement effect was not very obvious because the alumina and SAPO-34 molecular sieve were not mixed evenly, and it was difficult to effectively promote diffusion during the reaction, resulting in a low conversion rate of waste plastic raw materials and a low yield of light olefins.

[0253] In Comparative Example 7, since the surface of the all-silicon Silicalite-1 molecular sieve contains almost no acidic centers, the number of active acidic centers on the catalyst is small and the acidity is weak, resulting in a very low raw material conversion rate and an extremely low yield of light olefins.

[0254] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A spherical cracking catalyst, It is characterized in that The spherical cracking catalyst comprises a spherical precursor and a metal oxide. The spherical precursor comprises a SAPO-34 molecular sieve and alumina. Based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 20-50% by weight, and the content of the alumina is 50-80% by weight.

2. The spherical cracking catalyst according to claim 1, in, Based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 25-45% by weight, and the content of the alumina is 55-75% by weight; Preferably, based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 30-40% by weight, and the content of the alumina is 60-70% by weight.

3. The spherical cracking catalyst according to claim 1 or 2, in, The average particle diameter of the spherical precursor is 1.5-3.5 mm, and the average particle strength is 20-80 N / particle; Preferably, the average particle diameter of the spherical precursor is 2.2-2.8 mm, and the average particle strength is 28-55 N / particle; More preferably, the average particle diameter of the spherical precursor is 2.3-2.7 mm, and the average particle strength is 40-53 N / particle.

4. The spherical cracking catalyst according to any one of claims 1 to 3, in, The specific surface area of ​​the spherical precursor is 320-450m 2 / g, pore volume is 0.45-0.65mL / g; Preferably, the specific surface area of ​​the spherical precursor is 350-420m 2 / g, pore volume is 0.5-0.6mL / g; More preferably, the specific surface area of ​​the spherical precursor is 366-405m 2 / g, and the pore volume is 0.53-0.57mL / g.

5. The spherical cracking catalyst according to any one of claims 1 to 4, in, The preparation method of the spherical precursor comprises: (1) mixing an alumina precursor and a SAPO-34 molecular sieve and then ball milling the mixture to obtain a mixed powder; (2) contacting the mixed powder with an acidic aqueous solution to obtain a mixed sol; (3) dropping the mixed sol into an oil-ammonia column forming device, and subjecting the mixed sol to spherical gel after sphering and aging treatment; (4) The spherical gel is washed, dried and calcined to obtain a spherical precursor.

6. The spherical cracking catalyst according to claim 5, in, The ball milling conditions include: the speed of the grinding balls is 200-600 r / min, the temperature in the ball mill is 30-90° C., and the ball milling time is 5-50 h; And / or, the alumina precursor is selected from one or more of pseudo-boehmite, aluminum hydroxide gel, aluminum sol, gibbsite and boehmite; and / or, the weight ratio of the alumina precursor, the SAPO-34 molecular sieve and the acidic aqueous solution is 1:(0.1-1):(2.1-3); And / or, in step (3), the conditions for ball formation include: the sol ball dropping speed is 10-300 drops / minute, and the oil-ammonia column temperature is 20-120°C.

7. The spherical cracking catalyst according to any one of claims 1 to 6, in, Based on the total weight of the spherical cracking catalyst, the content of the spherical precursor is 93-99 weight %, and the content of the metal oxide is 1-7 weight %; Preferably, based on the total weight of the spherical cracking catalyst, the content of the spherical precursor is 94-98% by weight, and the content of the metal oxide is 2-6% by weight; More preferably, based on the total weight of the spherical cracking catalyst, the content of the spherical precursor is 95-97% by weight, and the content of the metal oxide is 3-5% by weight.

8. The spherical cracking catalyst according to claim 1 or 7, in, The metal oxide is selected from one or more of alkaline earth metal oxides, transition metal oxides and rare earth metal oxides; Preferably, the metal oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide, barium oxide, zinc oxide, copper oxide, cobalt oxide, cerium oxide, lanthanum oxide and zirconium dioxide.

9. The spherical cracking catalyst according to any one of claims 1 to 8, in, The specific surface area of ​​the spherical cracking catalyst is 300-430m 2 / g, the pore volume is 0.4-0.64mL / g, the pore size distribution is a bimodal distribution, and the most probable pore sizes corresponding to the bimodal distribution are 0.3-0.5nm and 7-12nm, respectively.

10. A method for preparing a spherical cracking catalyst, It is characterized in that The preparation method comprises: mixing a spherical precursor with an aqueous solution of a metal oxide precursor and carrying out a contact reaction; and then removing water, drying and calcining to obtain a spherical cracking catalyst, wherein the spherical precursor comprises a SAPO-34 molecular sieve and alumina, and based on the total weight of the spherical precursor, the content of the SAPO-34 molecular sieve is 20-50% by weight, and the content of the alumina is 50-80% by weight.

11. The preparation method according to claim 10, in, The metal oxide precursor is selected from inorganic salts containing alkaline earth metals, transition metals and rare earth metals; preferably, the metal oxide precursor is selected from nitrates containing magnesium, calcium, strontium, barium, zinc, copper, cobalt, cerium, lanthanum and zirconium; And / or, the mass concentration of the metal oxide precursor aqueous solution is 0.35-5.0%; and / or, the weight ratio of the spherical precursor to the aqueous solution of the metal oxide precursor is 1:(4-60); And / or, the contact reaction conditions include: temperature of 10-100° C., time of 0.5-50 h; And / or, the calcination conditions include: temperature of 400-700° C. and time of 2-20 h.

12. A spherical cracking catalyst prepared by the preparation method according to claim 10 or 11.

13. Use of the spherical cracking catalyst according to any one of claims 1 to 9 and 12 in the direct catalytic cracking of waste plastics to produce light olefins.

14. The use according to claim 13, in, The application comprises: contacting the spherical cracking catalyst with the powder of the waste plastic to react; Preferably, the contact conditions include: temperature of 420-580°C, pressure of 0.01-1MPa, and contact time of 0.5-12h; And / or, the weight ratio of the spherical cracking catalyst to the waste plastic powder is 1:(0.5-50).